Pentingnya Inovasi Dan Digitalisasi Pada UMKM Menuju Masyakarat Mandiri Di Desa Tanjung Agas Kabupaten Ogan Ilir Sumsel - Febriani, Yunita; Kalsum, Ummi; Fitria, Primasari; Permana, Araditya; Masdiana, Efrina; Gebby GS, Ayu; Rizki, Muhammad (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
MSMEs face increasingly complex challenges In the era of globalization, particularly in maintaining competitiveness. Innovation and digital marketing are key strategies that can help MSMEs capitalize on developments in expanding market reach, improving customer interaction, and creating competitive advantage. This PKM aims to provide mentoring in the concept of the importance of innovation in packaging and implementing digital marketing strategies by incorporating e-commerce to increase competitiveness. The Participatory Action Research (PAR) method was used, and its implementation involved the village government, a team of lecturers, and KKN students. The implementation results showed that innovation and digital marketing strategies were able to provide positive value in increasing sales value and sales through e-commerce media. Ultimately, digital marketing is not only a promotional tool, but also an innovative solution to support the growth of MSMEs in Tanjung Agas Village.